2016
DOI: 10.1371/journal.pone.0156524
|View full text |Cite
|
Sign up to set email alerts
|

GATA3 Expression Is a Poor Prognostic Factor in Soft Tissue Sarcomas

Abstract: ObjectiveRecent studies have investigated the significance of GATA3 expression in patients with various malignant tumors. However, no previous studies have evaluated the clinicopathological importance of GATA3 expression in soft tissue sarcomas (STS) patients.MethodsWe evaluated GATA3 expression in 76 STS cases using immunohistochemical analysis, and statistically compared clinicopathological characteristics between GATA3-positive and GATA3-negative cases.ResultGATA3-positive expression was significantly assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“… 10 However, GATA3 is a poor prognostic marker in neuroblastomas, endometrial carcinomas and soft tissue sarcomas. 11 , 12 , 14 The underlying mechanisms of the distinct function of GATA3 still remain unclear. It has been reported that, in breast cancer cells, GATA3 forms a complex with G9A/NuRD (MTA3) to suppress ZEB2 , TGFB1 and other epithelial-to-mesenchymal transition-related genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 10 However, GATA3 is a poor prognostic marker in neuroblastomas, endometrial carcinomas and soft tissue sarcomas. 11 , 12 , 14 The underlying mechanisms of the distinct function of GATA3 still remain unclear. It has been reported that, in breast cancer cells, GATA3 forms a complex with G9A/NuRD (MTA3) to suppress ZEB2 , TGFB1 and other epithelial-to-mesenchymal transition-related genes.…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 5 , 6 , 7 , 8 , 9 The association of GATA3 with human malignancies has been reported in breast cancers, neuroblastomas, endometrial carcinomas, urothelial carcinomas and soft tissue sarcomas. 10 , 11 , 12 , 13 , 14 However, its function remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous studies [ 19 23 ], patients were classified by sex, age (≤60 or >60 years), tumor size (≤5 cm or >5 cm), depth of tumor (superficial or deep), tumor location (extremities or trunk), the French Fédération Nationale des Centres de Lutte Contre le Cancer system (FNCLCC) grade (grade 1 or 2 or 3), tumor differentiation (score 1 or 2 or 3), mitotic count (0–9/10 or ≥10/10 high-power fields [HPF]), tumor necrosis (<50% or ≥50%), the American Joint Committee on Cancer (AJCC) stage (I or II or III), p53 expression (low or high), Ki-67 expression (low or high), and treatment (surgery alone or combined with postoperative therapy).…”
Section: Methodsmentioning
confidence: 99%
“…GATA3, a member of the GATA family (11,12), serves a crucial role in T-cell proliferation and differentiation (13). In addition, numerous studies have demonstrated that GATA3 serves different roles in different cancers, for example, GATA3 serves as a tumour activator in soft tissue sarcomas, endometrial carcinomas and neuroblastomas (14)(15)(16). In addition, GATA3 suppresses cell proliferation, migration and invasion in osteosarcoma (17).…”
Section: Introductionmentioning
confidence: 99%